Benzocyclobutene/vinylphenyl-introduced polycarbosilanes with low dielectric constant, high temperature performance and photopatternability. (1st June 2015) - Hu, Huan; Liu, Lili; Li, Zheng; Zhao, Cuijiao; Huang, Yawen; Chang, Guanjun; Yang, Junxiao
Abstract: With the development of microelectronic industry, low dielectric-constant insulating materials with high temperature performance and photopatternability have aroused interest. In this work, a kind of benzocyclobutene/vinylphenyl-introduced polycarbosilanes (PVBCS) were synthesized by H2 PtCl6 catalyzed ring-opening copolymerization of 4-(1-methylsilacyclobutyl) benzocyclobutene (4-MSCBBCB) and 1-methyl-1-(4-vinylphenyl) silacyclobutane (1-MVPSCB). By directly introducing photo-active groups on the pendants of polycarbosilanes, the PVBCS was endowed with photopatternability without additionally using any photo-initiators or photo-crosslinkers. DSC and FTIR characterization demonstrated that the PVBCS was UV&thermally curable. The UV curing was conducted at ambient temperature and the thermally curing was performed above 200 °C. TGA curves of the cured PVBCS indicated that the 5% weight loss temperature is 473 °C, which is above the required temperature limit. The cured PVBCS also has low dielectric constant of 2.32–2.40 in the range of 1 k∼1 MHz. The high temperature performance and low-dielectric constant could be attributed to the polycarbosilane main-chain structure and the benzocyclobutene-based cross-linked structure. Graphical abstract: